How to read the Bible book by book : a guided tour - Fee, Gordon D.; Stuart, Douglas K. (Grand Rapids, Mich. : Zondervan, 2002)
Narrative of Israel - Writings of Israel - Prophets of Israel - Gospels and acts - Epistles and revelation.
The Biblical Story: An Overview -- THE NARRATIVE OF ISRAEL IN THE BIBLICAL STORY -- Genesis -- Exodus -- Leviticus -- Numbers -- Deuteronomy -- Joshua -- Judges -- Ruth -- 1 and 2 Samuel -- 1 and 2 Kings -- 1 and 2 Chronicles -- Ezra-Nehemiah -- Esther -- THE WRITINGS OF ISRAEL IN THE BIBLICAL STORY -- Job -- Psalms -- Proverbs -- Ecclesiastes -- Song of Songs -- Lamentations -- THE PROPHETS OF ISRAEL IN THE BIBLICAL STORY -- Isaiah -- Jeremiah -- Ezekiel -- Daniel -- Hosea -- Joel -- Amos -- Obadiah -- Jonah -- Micah -- Nahum -- Habakkuk -- Zephaniah -- Haggai -- Zechariah -- Malachi -- THE GOSPELS AND ACTS IN THE BIBLICAL STORY -- Matthew -- Mark -- Luke -- Acts -- John -- THE EPISTLES AND REVELATION IN THE BIBLICAL STORY -- Romans -- 1 Corinthians -- 2 Corinthians -- Galatians -- Ephesians -- Philippians -- Colossians -- 1 Thessalonians -- 2 Thessalonians -- 1 Timothy -- 2 Timothy -- Titus -- Philemon -- Hebrews -- James -- 1 Peter -- 2 Peter -- 1 John -- 2 John -- 3 John -- Jude -- The Revelation.
Keywords: Bible -- Reading; Bible -- Criticism, interpretation, etc; Bible - Criticism, Interpretation, etc; Bible - Reading; Criticism, interpretation, etc